2022
DOI: 10.3390/ijms23105829
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophils Mediate Pulmonary Artery Thrombosis In Situ

Abstract: Pulmonary embolism is a life-threatening condition, which can result in respiratory insufficiency and death. Blood clots occluding branches of the pulmonary artery (PA) are traditionally considered to originate from thrombi in deep veins (usually in legs). However, growing evidence suggests that occlusion of the vessels in the lungs can develop without preceding deep vein thrombosis (DVT). In this work, we used an inferior vena cava (IVC) complete ligation model of DVT in Wistar rats to explore the possibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…VWF is stored in the Weibel-Palade bodies of the endothelium, and it is likely that MC-derived histamine, one of the most potent Weibel-Palade bodies secretagogues, stimulates its release in the COVID-19 setting. It has recently been shown that thrombi in the pulmonary artery can develop in situ ( 50 ), a process, in which VWF could be involved in the COVID-19 setting. Immuno-thrombosis mediated by MC accumulated in the lung septa has recently been reported using histopathology of post-mortem lung biopsies of patients with COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…VWF is stored in the Weibel-Palade bodies of the endothelium, and it is likely that MC-derived histamine, one of the most potent Weibel-Palade bodies secretagogues, stimulates its release in the COVID-19 setting. It has recently been shown that thrombi in the pulmonary artery can develop in situ ( 50 ), a process, in which VWF could be involved in the COVID-19 setting. Immuno-thrombosis mediated by MC accumulated in the lung septa has recently been reported using histopathology of post-mortem lung biopsies of patients with COVID-19 ( 44 ).…”
Section: Discussionmentioning
confidence: 99%
“…According to Peng et al [ 31 ], high neutrophil counts on admission were associated with intermediate- and high-risk acute PE and could serve as indicators of both inflammation and thrombosis associated with acute PE. The localized recruitment of neutrophils in the setting of DVT can contribute to the formation of thrombi in situ within the pulmonary vascular system [ 32 ]. On the one hand, neutrophils play a role in the formation of thrombi by expressing tissue factor and protein disulfide bond isomerase; on the other hand, highly activated neutrophils are capable of releasing neutrophil extracellular traps (NETs) into extracellular compartments where NETs act as scaffolds to support platelets and erythrocytes and interact with fibrin fibres to enhance thrombus stability, while histones H3 and H4, which are associated with NETs, directly contribute to platelet aggregation [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…Neutropenia was associated with a significant reduction in thrombus size in the inferior vena cava and delayed the transition from immature to mature fibrin and connective tissue formation within the thrombus. Animals with neutropenia had no thrombus in the pulmonary artery, and neutrophil ablation also eliminated macroscopic signs of lung injury [ 51 ].…”
Section: Discussionmentioning
confidence: 99%